French fries - Ransom, Candice F., 1952- (2019)
This book introduces readers to the history and culture associated with French fries, and it shows them they can make this favorite food at home. Vivid photographs and easy-to-read text aid comprehension for early readers. Features include a table of contents, an infographic, fun facts, Making Connections questions, a glossary, and an index. QR Codes in the book give readers access to book-specific resources to further their learning.
Potatoes -- Better than gold -- Who invented French fries? -- How to make French fries.
Includes index.
Ages 4-8
Keywords: French fries -- Juvenile literature; Junk food -- Juvenile literature; French fries; Junk food; Juvenile works